Clinical outcomes of patients receiving prolonged extracorporeal membrane oxygenation for respiratory support. (May 2019) - Na, Soo Jin; Jung, Jae-Seung; Hong, Sang-Bum; Cho, Woo Hyun; Lee, Sang-Min; Cho, Young-Jae; Park, Sunghoon; Koo, So-My; Park, Seung Yong; Chang, Youjin; Kang, Byung Ju; Kim, Jung-Hyun; et al.
Background: There are limited data regarding prolonged extracorporeal membrane oxygenation (ECMO) support, despite increase in ECMO use and duration in patients with respiratory failure. The objective of this study was to investigate the outcomes of severe acute respiratory failure patients supported with prolonged ECMO for more than 28 days. Methods: Between January 2012 and December 2015, all consecutive adult patients with severe acute respiratory failure who underwent ECMO for respiratory support at 16 tertiary or university-affiliated hospitals in South Korea were enrolled retrospectively. The patients were divided into two groups: short-term group defined as ECMO for ⩽28 days and long-term group defined as ECMO for more than 28 days. In-hospital and 6-month mortalities were compared between the two groups. Results: A total of 487 patients received ECMO support for acute respiratory failure during the study period, and the median support duration was 8 days (4–20 days). Of these patients, 411 (84.4%) received ECMO support for ⩽28 days (short-term group), and 76 (15.6%) received support for more than 28 days (long-term group). The proportion of acute exacerbation of interstitial lung disease as a cause of respiratory failure was higher in the long-term group than in the short-term group (22.4% versus 7.5%, p  < 0.001), and the duration of mechanical ventilation before ECMO was longer (4 days versus 1 day, p  < 0.001). The hospital mortality rate (60.8% versus 69.7%, p  = 0.141) and the 6-month mortality rate (66.2% versus 74.0%, p  = 0.196) were not different between the two groups. ECMO support longer than 28 days was not associated with hospital mortality in univariable and multivariable analyses. Conclusions: Short- and long-term survival rates among patients receiving ECMO support for more than 28 days for severe acute respiratory failure were not worse than those among patients receiving ECMO for 28 days or less.